Effect of Foveal Herniation on Surgical Outcomes of Idiopathic Epiretinal Membrane Peeling: A Challenging Presentation - Bravetti, Giacomo Edoardo; Mandrioli, Matteo; Cappuccini, Luca; Bravetti, Giorgio Enrico (Klinische Monatsblätter für Augenheilkunde, 2025)
Purpose The aim of this report is to describe the visual symptoms and spectral-domain optical coherence tomography (SD-OCT) findings associated with foveal herniation with epiretinal membrane and to evaluate the postoperative visual, anatomical, and surgical outcomes.Background Foveal herniation occurs when neuroretinal tissue protrudes through and above the level of an epiretinal membrane. The pathogenesis of foveal herniation is still unknown, though it is likely attributable to the centripetal contraction of the epiretinal membrane (ERM). Moreover, thinning of the prefoveolar internal limiting membrane (ILM) may further exacerbate this process by reducing the structural support for the retina in that area. In the literature, foveal herniation with ERM is rare and usually described as unilateral. Most cases present a good visual outcome after surgical intervention.Case Description We describe the case of a 37-year-old Caucasian male patient, without any previous ocular history, who presented with metamorphopsia and a sustained reduction visual acuity to his left eye that had persisted for several months. The baseline best-corrected visual acuity (BCVA) was recorded as 0.05 decimals. Anterior segment examination was unremarkable, while dilated fundoscopy revealed an ERM with a concentric ring of foveal tissue prolapse. SD-OCT showed the foveal tissue protruding through and above the ERM, demonstrating the severe foveal herniation. A diagnosis of idiopathic ERM with foveal herniation was established based on these findings. Subsequently, the patient was scheduled for surgical intervention to undergo pars-plana vitrectomy with ERM peeling. After the surgery, the patient experienced progressive restoration of the foveal anatomy and an improvement of vision to 0.6 decimals from baseline at 3 months.Conclusion This case report shows a rare finding of foveal herniation with ERM. This atypical presentation is of important clinical relevance in drawing cliniciansʼ attention to the possibility of these findings, with the goal to prevent erroneous diagnosis and unnecessary treatments. We demonstrate the visual improvement and gradual resolution of foveal herniation with SD-OCT images after ERM removal, and the images show that it may take a few months for the foveal bulge to decrease in height. When the outer retinal layers are normal, visual recovery, though delayed, is appreciable.
Keywords: epiretinal membrane; foveal herniation; macular surgery; optical coherence tomography; flower-petal peeling